The relationship between transport, economic growth and environmental degradation for ninety countries - Listiono, Listiono (Centre for Science and Technology, IAIN Surakarta, 2018)
This paper investigates the relationship between freight transport, economic growth and environmental degradation (CO2 emissions) experienced by ninety countries over the period 1980-2014. The estimation is divided into the global panel, high-income countries, upper-middle income countries, lower-middle income countries, and lower-income countries. This paper employed simultaneous equation Model and was estimated by Three-Stage Least Squares (3SLS). The results discovered the existence of bi-directional causality relationship between economic growth and freight transport in the high-income countries and lower-income countries. The result also indicated the bi-directional causality relationship between the transportation and CO2 emissions in the panel upper-middle-income countries. Lastly, the finding indicated the bi-directional causality between economic growth and CO2 emissions in lower-middle income countries.